2018
DOI: 10.1038/s41467-018-06181-6
|View full text |Cite
|
Sign up to set email alerts
|

Spin dynamics of the block orbital-selective Mott phase

Abstract: Iron-based superconductors display a variety of magnetic phases originating in the competition between electronic, orbital, and spin degrees of freedom. Previous theoretical investigations of the multi-orbital Hubbard model in one-dimension revealed the existence of an orbital-selective Mott phase (OSMP) with block spin order. Recent inelastic neutron scattering (INS) experiments on the BaFe2Se3 ladder compound confirmed the relevance of the block-OSMP. Moreover, the powder INS spectrum revealed an unexpected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
60
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 61 publications
7
60
1
Order By: Relevance
“…This conclusion agrees with our recent theoretical studies in n = 5.5 iron Te-based ladders [21]. Because many believe that the Block-type magnetic order of BaFe 2 Se 3 is related to an orbital selective Mott state induced by electronic correlations [28,[31][32][33], it is reasonable to conclude that BaFe 2 Te 3 could also display this interesting state as well. Of course, more powerful manybody techniques based on multiorbital Hubbard models are required to confirm this OSMP hypothesis.…”
Section: Magnetismsupporting
confidence: 92%
See 1 more Smart Citation
“…This conclusion agrees with our recent theoretical studies in n = 5.5 iron Te-based ladders [21]. Because many believe that the Block-type magnetic order of BaFe 2 Se 3 is related to an orbital selective Mott state induced by electronic correlations [28,[31][32][33], it is reasonable to conclude that BaFe 2 Te 3 could also display this interesting state as well. Of course, more powerful manybody techniques based on multiorbital Hubbard models are required to confirm this OSMP hypothesis.…”
Section: Magnetismsupporting
confidence: 92%
“…For example, the existence of an "orbital-selective Mott phase" (OSMP) was found by neutron experiments at ambient pressure [30]. This OSMP of BaFe 2 Se 3 was theoretically discussed based on DMRG methods by using multiorbital Hubbard models as well [31][32][33]. However, an additional striking experimental discovery was recently reported for this interesting material: the existence of a polar state with possible polar orbital ordering was confirmed by neutron diffraction methods combined with optical second harmonic generation signals [34].…”
Section: Introductionmentioning
confidence: 99%
“…Similar patterns were also reported in two dimensions with iron vacancies, such as in Rb 0.89 Fe 1.58 Se 2 [14] and K 0.8 Fe 1.6 Se 2 [8,[15][16][17]. For the aforementioned compounds the OSMP state is believed to be relevant [8,13,[18][19][20].Recent theoretical investigations [21,22] showed that a multi-orbital Hubbard model in the OSMP state properly describes the INS spin spectra of π/2-block state of powder BaFe 2 Se 3 [13]. However, the origin of block magnetism and its relation to the OSMP is an intriguing and generic question that has been barely explored.…”
supporting
confidence: 66%
“…It is currently unknown if the latter approximates a pseudogap or rather a weak insulator, and more detailed analysis is needed.Block magnetism. Previous efforts [21,22] showed that the OSMP can display exotic magnetic properties, such as AFM coupled FM islands (the spin-block phase).Here, one of our main results is that the magnetic pattern of the block-OSMP is not limited to the π/2-phase, but remarkably the OSMP can support a variety of spin patterns previously unknown. Figure 2(a) illustrates the filling n dependence of the total spin structure factor S(q) [35].…”
supporting
confidence: 53%
“…To date, multiband electronic structure is proven to be of crucial importance in rather versatile superconducting systems, such as MgB 2 [10], iron-based compounds [11][12][13][14][15][16], superconducting nanostructures [17][18][19][20][21], 2D electron gases at interfaces [22][23][24], metal-organic superconductors [25][26][27], etc. In such multiband superconductors, the pairing interaction and the proximity/hybridization of two or more bands can result in the formation of Cooper pairs with electrons originating from different bands, a phenomenon termed "cross-band pairing" or simply "crosspairing".…”
mentioning
confidence: 99%